Safety of Nighttime 2-Hour Suspension of Basal Insulin in Pump-Treated Type 1 Diabetes Even in the Absence of Low Glucose - Sherr, Jennifer L. (American Diabetes Association, 2014)
OBJECTIVE: An integrated sensor-augmented pump system has been introduced that interrupts basal insulin infusion for 2 h if patients fail to respond to low-glucose alarms. It has been suggested that such interruptions of basal insulin due to falsely low glucose levels detected by sensor could lead to diabetic ketoacidosis. We hypothesized that random suspension of basal insulin for 2 h in the overnight period would not lead to clinically important increases in blood β-hydroxybutyrate levels despite widely varying glucose values prior to the suspension. RESEARCH DESIGN AND METHODS: Subjects measured blood glucose and blood β-hydroxybutyrate levels using a meter each night at 9:00 p.m., then fasted until the next morning. On control nights, the usual basal rates were continued; on experimental nights, the basal insulin infusion was reprogrammed for a 2-h zero basal rate at random times after 11:30 p.m. RESULTS: In 17 type 1 diabetic subjects (mean age 24 ± 9 years, diabetes duration 14 ± 11 years, A1C level 7.3 ± 0.5% [56 mmol/mol]), blood glucose and blood β-hydroxybutyrate levels were similar at 9:00 p.m. on suspend nights (144 ± 63 mg/dL and 0.09 ± 0.07 mmol/L) and nonsuspend nights (151 ± 65 mg/dL and 0.08 ± 0.06 mmol/L) (P = 0.39 and P = 0.47, respectively). Fasting morning blood glucose levels increased after suspend nights compared with nonsuspend nights (191 ± 68 vs. 141 ± 75 mg/dL, P < 0.0001), and the frequency of fasting hypoglycemia decreased the morning following suspend nights (P < 0.0001). Morning blood β-hydroxybutyrate levels were slightly higher after suspension (0.13 ± 0.14 vs. 0.09 ± 0.11 mmol/L, P = 0.053), but the difference was not clinically important. CONCLUSIONS: Systems that suspend basal insulin for 2 h are safe and do not lead to clinically significant ketonemia even if the blood glucose level is elevated at the time of the suspension.